Private Sector Consultation on Climate Smart Agriculture: The Feed the Future Learning Community for Supply Chain Resilience - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Smallholder farmers around the globe are facing unstable productivity due to changing climate and weather patterns. The ways in which the private sector supports these farmers to build resilience to climate change and/or engage in efforts to mitigate climate change can have significant impact on the ability for farmers to make a living, the security of supply of smallholder crops, and the reputation of the private sector actors drawing loyalty of end consumers and investors. As part of an effort to better engage the private sector in climate smart agriculture activities the Learning Community for Supply Chain Resilience, funded by USAID’s Feed the Future program and in support of the Alliance for Resilient Coffee (ARC), interviewed 18 coffee companies to better understand how they think about climate risk and climate smart agriculture, the types of activities in which they engage, and the types of climate information they use and/or need1. The results of this study are supplemented by results from a case study of Ugandan coffee companies, illustrating how their use of and need for climate information differs at the national level. The results give insight into the types of information that private sector companies are looking for to be able to design and implement effective climate smart agriculture programs. It also yields some insight on information and tools that would facilitate sector-level strategies. While all of the companies interviewed are engaged in sustainable agriculture activities, there is confusion in the sector about the definition of “climate smart agriculture” and which activities fall under that category rather than the broader “sustainability” category. Companies that worked closely with farmers, tended to not separate efforts into climate or sustainability efforts, but rather focused on holistic programs to increase productivity and make farming a viable option for today’s farmers and an attractive option for the next generation. Companies in the study used a variety of types of climate information depending on their needs, which were seen to have more relation to their distance to smallholder farmers rather than position in the supply chain as a trader or roaster. The proximity to farm level along with results on drivers for decision-making, motivations for investing in climate smart practices (focus on security of supply or brand reputation) and influencers (integration of sustainability staff with procurement/sourcing or strong company values) all informed our categorization of different types of companies. For this paper, we are using three categories of (i) “direct service providers” (those providing integrated services to smallholder farmers), (ii) “collaborators” (those working with direct service providers to support work with smallholder farmers), and (iii) “catalysts” those working at global, sector or policy level on climate issues with a light touch at the farm level. These categories are intended to serve as general guideposts as the Alliance for Resilient Coffee and other partners develop and tailor tools and analyses for different audiences. Companies working closest to smallholder farmers (direct service providers) had the most access to and need for detailed farm-level data, and are looking for more local information to supplement their knowledge, such as changing local weather patterns, site-specific good agricultural practices (GAPs) and recommendations for adaptation practices for particular climate hazards. Those working with the direct service providers (the collaborators) depend on the direct service providers for information to shape their program design and implementation. These companies often work in collaborations at a slightly higher level, looking to area-specific climate maps and case studies on successful programming to inform a broader strategy. Those furthest from the farm level, (the catalysts) rely on secondary sources of information from sector groups, such as backbone organizations and trade groups, as well as suppliers and desk research to answer particular questions and develop strategy. Although differing depending on their role in the supply chain, there were several types of information that many of the companies were interested in using and felt were missing to make decisions about climate smart activities. These included (i) quality, site-specific information for improved diagnostics, (ii) information to help measure and manage climate risk and (iii) information related to specific, practical technologies to build resilience. There was also a common call from all companies for easier access to quality, digestible information and fewer long, academic papers that are hard to find the time to read. One of the key findings of this study is that in order to successfully approach companies and tailor tools and resources to their needs, tool/resource developers need to understand the role of climate smart agriculture within their business model and sustainability strategy, their motivations for investing in climate smart agriculture and the types of tools and resources that would most benefit them. This study is a deep dive into the drivers for climate investments by a subset of global coffee companies and as such not a comprehensive, definitive picture of the state of the entire industry. However, through conversations with the first mover companies, it is clear that climate change is a recognized and present issue with all companies regardless of position in the value chain. There was no reticence or denial of the severity of the threat nor a lack of recognition of the potential impact to companies’ bottom line from climate change among those interviewed. There was rather an almost universal engagement and enthusiasm that the sector – companies, farmers, government, donors, research, NGOs – must tackle this threat together and act fast. There was a sense of urgency and even impatience from some that the strategies and programs must be better coordinated, informed by credible science and rigorously practical for farmers’ realities. With access to the right information in the right format, coffee companies will be more likely to utilize tools and resources to make informed decisions in the face of climate change.